C-phycocyanin alleviated cisplatin-induced oxidative stress and inflammation via gut microbiota—metabolites axis in mice - Zhang, Yubing; Li, Lili; Qin, Song; Yuan, Jingyi; Xie, Xiaonan; Wang, Fan; Hu, Shanliang; Yi, Yuetao; Chen, Min (Frontiers in Nutrition, 2022)
C-phycocyanin is a natural protein extracted from Spirulina platensis. We aim to investigate the preventive effect of C-phycocyanin on cisplatin chemotherapy-induced oxidative damage and inflammation.The result showed that C-phycocyanin treatment reduced cisplatin induced mortality and inflammation including decreased levels of serum IL6, kidney MCP1 and liver IL1β. Furthermore, C-phycocyanin also exerted antioxidant effects on mice, including increased GSH-Px, GGT and GSH levels in liver and increased CAT and SOD levels in kidney. HepG2 cells experiments showed that C-phycocyanin exhibited none of prevention effects on cisplatin injury. Cisplatin demonstrated the greatest reduction on the abundance of Faecalibaculum genus, which was related with the enrichment of Romboutsia and Lactobacillus genus. C-phycocyanin treatment reduced the populations of harmful bacteria of Enterococcus faecalis, which was positively correlated with cisplatin induced inflammation. C-phycocyanin increased the contents of 23-nordeoxycholic acid and β-muricholic acid. Moreover, C-phycocyanin increased amino acid related metabolites Nα-acetyl-arginine and trimethyl-lysine contents, decreased inflammatory biomarker of FAHFAs content. In conclusion, C-phycocyanin inhibited inflammation via 23-nordeoxycholic acid-Enterococcus faecalis-inflammation axis, enhanced the antioxidant capacity of kidney via Lactobacillus-NRF2 pathway. C-phycocyanin alleviated cisplatin injury via the modulation of gut microbiota especially Lactobacillus and Enterococcus, as well as regulation of metabolites especially bile acid and FAHFA, which highlight the prebiotic effect of C-phycocyanin and provides a new strategy to prevent cisplatin injury.